AGENT-BASED MODELING OF CONSUMER BEHAVIOR ON DAIRY MARKET - Yuliya Sergeevna Otmakhova (Science and Innovation Center Publishing House, 2020)
The problems of divergent interests of food market participants lead to various transformations of consumer demand and actualize the need to research and determine various strategies for consumer behavior in the markets of socially significant food products. The paper presents the author’s approach to building an agent-based model of consumer behavior in the dairy market in terms of information asymmetry and limited rationality of agents. The results of the conducted computable experiments allowed us to demonstrate the strategies of consumer behavior with changes in such factors as food preferences, price level, frequency of purchase, the degree of adherence to the principles of healthy eating, brand loyalty, and the degree of susceptibility of advertising information.